“Estudio técnico económico de una planta agroindustrial de tableros de partícula a partir de especies forestales no comerciales en picota Región San Martín - Maldonado Cardenas, Jimmy Carlix (2004)
The Region San Martín has a production area very important, of natural production forest, capable of supplying roundwood, non-commercial, for producing agglomerated particle board, oriented for consumption in the domestic market, the raw material is located in the basin of the Chaipichotal River and surroundings in the area of Biaba, in general is an area of more than 100,000 Has. with a production of more than 13'500, 000 m3 (r) of wood volume. Particle boards is currently imported from the sister Republic of Ecuador, and according to the literature review carried out in this study found 0.936 kg/inhabitants/year consumption. The demand potential unmet annual, to level national, is estimated in 17861 T.M. that corresponds to 57.84% of demand unsatisfied for the consumption national, only is is covering the market national with 42.16% with products of Maderba and with boards of particles imported of educator. Is plant...